(untitled) (Research, Society and Development, 2021)
In recent years, it has been observed a significant expansion of the organic market. In this context, the main phytosanitary problem of soybean in the organic system is Asian rust (Phakopsora pachyrhizi), for which it is difficult to control, considering the restriction of products authorized for use in the organic system and the limitation of research related to this management system. The objective of this study was to evaluate the effect of alternative products on the germination of uredospores, on the severity of soybean rust on detached leaves and the control of the disease under greenhouse and field conditions. The alternative treatments were calcium silicate, lime sulphur, bordeaux mixture, and copper oxychloride. The variables analyzed were uredospores germination, disease severity, defoliation level, area under the disease progress curve (AUDPC), a thousand grain mass and productivity. The results obtained indicate that there is a possibility of using copper oxychloride to manage the Asian rust in organic production systems. Copper oxychloride had reduced the germination of uredospores and when evaluated under controlled conditions using detached leaves and greenhouse, it had reduced the severity of the disease. In field conditions, copper oxychloride at the doses of 588 and 882 g ha-1 reduced severity and AUDPC, in addition to increasing productivity at 1434 kg ha-1 in relation to the control. It is concluded that copper oxychloride can be used as a tool in the management of Asian rust in organic systems of soy production.